Microfluidic generation of encapsulated droplet interface bilayer networks (multisomes) and their use as cell-like reactors. Issue 35 (8th April 2016) - Elani, Yuval; Solvas, Xavier C. I.; Edel, Joshua B.; Law, Robert V.; Ces, Oscar
Abstract : Using a microfluidic device to incorporate bilayer networks inside droplets, we generate compartmentalised cell-like microreactors based on lipid membranes. Abstract : Compartmentalised structures based on droplet interface bilayers (DIBs), including multisomes and compartmentalised vesicles, are seen by many as the next generation of biomimetic soft matter devices. Herein, we outline a microfluidic approach for the construction of miniaturised multisomes of pL volumes in high-throughput and demonstrate their potential as vehicles for in situ chemical synthesis.